RESEARCH ON THE USABILITY OF GAMES FOR THE INTERVENTION OF KOREAN DYSLEXIA - FOCUSING ON COUNTING GAMES – - Park , Inchan; Kim , Songyi (PEOPLE: International Journal of Social Sciences, 2018)
It is estimated that around 5% of the Korean population, or about 2,500,000 people, have dyslexia. For the purpose of developing a functional dyslexia intervention, online phonological awareness games that focus on counting syllables and phonemes have been developed. In this research, a usability test was conducted to evaluate two such games. A checklist was developed based on the test results of the User Interface experts. The checklist consisted of 10 questions to be answered by students and 18 questions for clinicians. The subjects for the usability test comprised 21 students and 22 clinicians. A test platform was developed to provide a test environment that was conducive to playing online games. The analysis of the usability test results has been grouped into two parts: a quantitative analysis and a qualitative analysis. Based on the quantitative analysis results, the dyslexic students averaged 8.5 points (±1.53) on a Likert Scale of 10; while the dyslexia clinicians averaged 8.7 points (±0.87) on the same Likert Scale. Based on the results of the qualitative analysis, an enhancement of the rewards function, a better user interface for the button used to check for the correct answer, and a button to enlarge the screen were identified as areas for improvement. In the future, the requirements of the test subjects and the stakeholders will be taken into consideration, and the games will be improved accordingly.